Improving output current of inductor-cell based five-level CSI using hysteresis current controller - Suroso Suroso; Winasis Winasis; Priswanto Priswanto; Sholikhah Sholikhah (Institute of Advanced Engineering and Science, 2021)
Current source inverter (CSI) operates to output a specified ac current waveform from dc current sources. Talking about power quality, harmonics distortion of ac waveform is a problem of an inverter circuit. Generating a multilevel current waveform will have less harmonics content than a traditional three-level current waveform. In addition to non-ideal conditions of power switches, i.e. voltage drop in diodes, conductors or controlled switches, the performance of current controller applied in an inverter circuit will considerably affect the ac waveform quality produced by inverter circuit. This paper presents and discusses application of hysteresis current controller in the five-level H-bridge with inductor-cell current source inverter. The current controller performance was compared with the proportional integral current controller. Some test results are presented and discussed to explore the advantages of hysteresis controller in reducing the current ripple and harmonics distortion of output current.